2021
DOI: 10.1021/acssuschemeng.0c06108
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Release of Orthophosphate by Fe-Modified Biochars: Mechanisms and Environmental Applications

Abstract: Biochars have been suggested to have P capture potential from effluent streams and to recycle the captured P to agricultural soils. However, most biochars have low P sorption capacity. The objective of this study was to engineer biochar for enhanced P sorption affinity. Biochar was produced from corn stover biomass pre-treated with FeSO4 (ISIB) using autothermal (air-blown) pyrolysis at 500°C. Point of zero charge (pHZPC) shifted from 8.48 to 4.31 indicating that Fe treatment increased dominance of acid functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…In the current study, the difference between manure Mehlich-P and manure-biochar suggests that the applied P in manure-biochar could be associated with the mineral phases of biochar or associated with biochar-OM, not evaluated or reported in this study. The lowest P content of Mehlich3-P in Fe-modified biochar among all manure-biochar treatments suggests a P sorption on oxy-hydroxide phases of Febiochar (Bakshi et al, 2019, Bakshi et al, 2021 was not extracted with Mehlich3.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the difference between manure Mehlich-P and manure-biochar suggests that the applied P in manure-biochar could be associated with the mineral phases of biochar or associated with biochar-OM, not evaluated or reported in this study. The lowest P content of Mehlich3-P in Fe-modified biochar among all manure-biochar treatments suggests a P sorption on oxy-hydroxide phases of Febiochar (Bakshi et al, 2019, Bakshi et al, 2021 was not extracted with Mehlich3.…”
Section: Discussionmentioning
confidence: 99%
“…Manure application to soil significantly increased M3-P under both corn and soybean; besides, no biochar manure mixture treatments significantly increased the M3-P. A relatively low M3-P for MHAPE treatment among all biochar manure treatments under corn may have resulted from specific adsorption of soil-P onto the biochar Fe surface, making the P less available in the soil [16]. Allen and Mallarino (2008) [5] reported that multiple manure application in a conventional way overloads the soil P; however, the application of manure-biochar mixture in this research showed that it could lower plant-available P loss from soil and resolve manure management issues.…”
Section: Discussionmentioning
confidence: 94%
“…The high affinity of Fe oxide hydroxide for P [13,14] has inspired researchers to use Fe surfaces as P removing strategy from P contaminated systems [15]. These observations have also prompted surface-modified biochar research to enhance the sorption of oxyanions onto biochar surfaces via complexation and ligand exchange reactions to develop P removal or release strategies [16][17][18][19]. We recently reported that surface-modified Fe-biochar application also showed low soil heavy metal concentrations without compromising crucial plant-available soil nutrients upon manure application [20].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of manure treatment applied to the soil followed the 135 kg/ha (120 lb/ac) recommended rate for P. The decision on the amount of manure and manure-biochar mixture addition as a treatment was challenging as they had a different amount of macro-and micro-nutrients at the end of the manure-biochar incubation. We considered (factor 1): the plant-available P content of organic fertilizer as one of the crucial plant nutrients, and (factor 2) the greater affinity of Fe-pretreated biochars for P in the HAPE biochar [16] than RO or HAP feedstock biochars. Specifically, these two important factors are considered to alleviate the variability and complexity among the biochar-manure mixtures.…”
Section: Soil Preparation Greenhouse and Pot Experimentsmentioning
confidence: 99%
“…The high affinity of Fe oxide hydroxide for P [13,14] has inspired researchers to use Fe surfaces as P removing strategy from P contaminated systems [15]. These observations have also prompted surface-modified biochar research to enhance the sorption of oxyanions onto biochar surfaces via complexation and ligand exchange reactions to develop P removal or release strategies [16][17][18][19]. We recently reported that surface-modified Fe-biochar application also showed low soil heavy metal concentrations without compromising crucial plant-available soil nutrients upon manure application [20].…”
Section: Introductionmentioning
confidence: 99%